中国10个地区老年人长寿影响因素的前瞻性队列研究 - Li, S; Zhang, Y; Xiao, M; Sun, D; Yu, C; Wang, Y; Pei, P; Chen, J; Chen, Z; Li, L; Lyu, J (Zhonghua Yixuehui, Chinese Medical Association, 2024)
Objective To evaluate the associations of sociodemographic characteristics and lifestyle factors with longevity status in older adults in China.